Association Between Tumor Mutation Profile and Clinical Outcomes Among Hispanic-Latino Patients With Metastatic Colorectal Cancer - Philipovskiy, Alexander; Ghafouri, Reshad; Dwivedi, Alok Kumar; Alvarado, Luis; McCallum, Richard; Maegawa, Felipe; Konstantinidis, Ioannis T.; Hakim, Nawar; Shurmur, Scott; Awasthi, Sanjay; Gaur, Sumit; Corral, Javier (Frontiers in Oncology, 2022)
In the United States, CRC is the third most common type of cancer and the second leading cause of cancer-related death. Although the incidence of CRC among the Hispanic population has been declining, recently, a dramatic increase in CRC incidents among HL younger than 50 years of age has been reported. The incidence of early-onset CRC is more significant in HL population (45%) than in non-Hispanic Whites (27%) and African-Americans (15%). The reason for these racial disparities and the biology of CRC in the HL are not well understood. We performed this study to understand the biology of the disease in HL patients. We analyzed formalin-fixed paraffin-embedded tumor tissue samples from 52 HL patients with mCRC. We compared the results with individual patient clinical histories and outcomes. We identified commonly altered genes in HL patients (APC, TP53, KRAS, GNAS, and NOTCH). Importantly, mutation frequencies in the APC gene were significantly higher among HL patients. The combination of mutations in the APC, NOTCH, and KRAS genes in the same tumors was associated with a higher risk of progression after first-line of chemotherapy and overall survival. Our data support the notion that the molecular drivers of CRC might be different in HL patients.